EJ12 girl hero: making waves - MCFARLANE, SUSANNAH; SUSANNAH MCFARLANE (New York Scholastic, 2010)
10-year-old Emma Jacks, a secret spy, tackles a mission to save a coral reef from the evil SHADOW agency.
Keywords: seventh book in the EJ12 Girl Hero adventure series written by Susannah McFarlane; bravery, self-belief, and overcoming personal fears